(untitled) (Revista Educação, Artes e Inclusão, 2021)
This article dicusses the insertion of deaf culture in na inclusive school system, in both early childhood education and art teaching. We have looked at the work of deaf artist Nancy Rourke and selected eight of the diferente works of hers produced from 2010 to 2012, which have dealt with identity, otherness and difference. The present research is exploratory in nature, with a quantitative approach, besides to have a bibliographic character. The respective studies have allowed us to undestand art class as a privileged space that has produced rich opportunities of job with diferent characteristics of the human being. Therefore, it is relevant that teacher knows the Works of the artist and creates in his or her classrrom pedagogical and fair activities to each group, in order to allow their students, by means of art, know and discuss the human diversity portrayed on the painting. According to the view of above, we concluded that working with art teaching in early childhood education enables us to start the process of a esthetic appreciation and the formation of a more open society, and prepared for na experiency from the perspective of human diversity.